Strategi Pengawasan Pemilu: Pola Penanganan Pelanggaran Kampanye oleh Bawaslu Provinsi di Wilayah Urban Kota Palangka Raya - Cantika Cantika; Wening Mustikaningsih (Indo Publishing, 2026)
This study analyzes the strategies and effectiveness of the Election Supervisory Board (Bawaslu) of Central Kalimantan Province in monitoring campaign violations in the 2024 Gubernatorial and Deputy Gubernatorial Election, focusing on the urban area of Palangka Raya City. The objective of the present study is to evaluate the patterns of handling violations, considering Palangka Raya as the political center of the province with the highest vulnerability. This includes violations of campaign props (APK) zoning, campaign schedules, civil servants' neutrality, and money politics. This is of paramount importance to maintaining the integrity of democracy and ensuring fairness among contestants. This research method employs a descriptive qualitative approach through a case study conducted from September to December 2025, with primary data from interviews with key informants (Bawaslu Legal Division, Gakkumdu, volunteers) and secondary data from regulations such as Law No. 7/2017. The analysis employs the Miles-Huberman model, incorporating triangulation to ensure validity. The findings of this research indicate that violations were predominantly characterized by administrative issues, such as the use of illegal campaign props, and breaches of the organizers' code of ethics, accounting for a total of two primary cases. There were no significant election-related criminal offenses observed. Bawaslu implements a multifaceted supervisory approach, encompassing preventive measures such as participatory socialization, reactive measures including field patrols, and a collaborative element involving Gakkumdu and volunteers. However, this approach is constrained by a 7-day handling time and vertical coordination. The primary contribution of this research is the analysis of the synchronization between provincial and city Bawaslu in the context of the 2024 regional elections in urban areas, recommending reforms in time management and human resources for optimal effectiveness